2010
DOI: 10.1111/j.1365-2796.2009.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between renal function, presentation, use of therapies and in‐hospital complications in acute coronary syndrome: data from the SWEDEHEART register

Abstract: Sweden) Relation between renal function, presentation, use of therapies and in-hospital complications in acute coronary syndrome: data from the SWEDE-HEART register. J Intern Med 2010; 268: 40-49.Objective. To examine clinical characteristics, presenting symptoms, use of therapy and in-hospital complications in relation to renal function in patients with myocardial infarction (MI).Design. Observational study. Subjects. Consecutive MI patients with available creatinine (n = 57 477).Results. Glomerular filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 23 publications
6
94
2
7
Order By: Relevance
“…Our analysis found that MI patients differ in their clinical and angiographic characteristics, depending on their IRF grade, consistent with the findings of other studies [5][6][7][8][12][13][14][15][16]. In patients with worse IRF, there is a greater percentage of predictors of poorer prognosis.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our analysis found that MI patients differ in their clinical and angiographic characteristics, depending on their IRF grade, consistent with the findings of other studies [5][6][7][8][12][13][14][15][16]. In patients with worse IRF, there is a greater percentage of predictors of poorer prognosis.…”
Section: Discussionsupporting
confidence: 81%
“…The populations of patients with particular IRF grades noted in our analysis are comparable with the data from the GRACE [5], ACS I/II [5], and SWEDEHEART [7] registries. The observed differences between the studies result from the adopted definitions of renal dysfunction and criteria use to select and stratify the analysed population.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Choć pacjentów z przewlekłą chorobą nerek (CKD) charakteryzuje gorsze rokowanie w NSTE-ACS niż osoby z prawidłową funkcją nerek, to rzadziej są oni poddawaniu leczeniu zgodnemu z medycyną opartą na faktach, obejmującemu leki przeciwzakrzepowe i wczesną strategię inwazyjną [446,447]. Rozpoznanie NSTE-ACS u pacjentów z CKD może być trudniejsze ze względu na często obserwowane, łagodnie podwyższone stężenie troponin sercowych i nieprawidłowości w EKG (np.…”
Section: Przewlekła Choroba Nerekunclassified
“…Пациенты с ОПП 1,12-1,27, p<0,001) и 6-месячной (ОР 1,16, 95% ДИ 1,11-1,22, p<0,001) смертности [70]. Пациенты с ОКС, имеющие нарушение функции почек, часто не получают адекватную терапию [71,72], что объясняется как отсутствием данных о клинических исследованиях в этой популяции, так и высоким риском осложнений, прежде всего кровотечений и дальней-шего ухудшения функции почек. Есть данные, что у больных ХБП часто развиваются кровотечения вслед-ствие передозировки антитромботических препаратов, дозы которых, при преимущественно почечном пути выведения, нуждаются в коррекции с учетом функцио-нального состояния почек (табл.…”
Section: острое повреждение почек при острой сердечной недостаточностunclassified